이주의 시대, 사민주의 복지체제의 유효성: 이주민의 노동시장 통합성을 중심으로 - 조형규; Hyung Kyu Jo; 윤홍식; Hong Sik Yoon (다문화와 평화, 2021)
본 연구는 사민주의 복지체제를 중심으로 노동시장에서 복지노력과 이주민통합노력이 이주민노동시장 통합성과에 미치는 영향과 복지체제별 차별성을 분석하였다. OECD 13개국을 대상으로 2007년부터 2017년까지의 국가별 패널자료를 활용하여 기술통계분석과 패널회귀분석을 실시하였다. 기술통계 분석결과, GDP 대비 적극적노동시장지출 비율, 기타지출 비율 및 MIPEX 노동시장이동성지수가 사민주의체제에서 가장 높았다. 사민주의체제의 통합성과는 임시직근로자비율 측면에서 중간수준, 근로빈곤율 측면에서 높은 수준임을 확인하였다. 패널회귀 분석결과, MIPEX 노동시장이동성지수와 차별금지지수로 측정한 이주민통합노력 수준이 높을수록 임시직근로자비율 측면에서 이주민 통합성과가 개선되었다. 또한, MIPEX 노동시장이동성지수가 높을수록 근로빈곤율 측면의 이주민 통합성과에 긍정적인 영향을 미치는 것을 알 수 있었다. 남유럽체제와의 비교를 제외하고 노동시장에서 사민주의체제의 통합성과는 다른 복지체제보다 열악하였다. 이는 국민국가에 기초한 복지국가가 이주민의 사회적 위험을 해소하기에는 부적합한 체제일 수 있다는 것을 의미한다. This study analyzed the effects of welfare and integration efforts for migrants on the integration outcomes of migrants in the labour market and the differentiation of each welfare regime, focusing on social democratic regime. Using national panel data from 2007 to 2017 of 13 OECD countries, descriptive statistics analysis showed the MIPEX labour market mobility index as well as the public social expenditure of active labour market and other social policy area as a percent of GDP were the highest in the social democratic regime. The integration outcome of the social democratic regime was moderate in terms of temporary employment rate and high in terms of the working poverty rate. Panel regression analysis showed the higher migrant integration efforts of the MIPEX(labour market mobility and anti-discrimination) improved the integration outcome in terms of temporary employment rate. Moreover, the higher MIPEX(labour market mobility) had a positive effect on the integration of working poor migrants. Except for the comparison with the southern european regime, the integration outcome of the social democratic regime was inferior to those of other regimes in the labour market which means a welfare state based on a nation-state might be an inappropriate system to address social risks of migrants.